Qualitative and quantitative studies on two commercial specifications of Polygonatum odoratum - Nan, Yi; Liang, Haizhen; Pang, Xu; Zheng, Wei; Shi, Yuhao; Chen, Xiaojuan; Zhang, Jie; Song, Juan; Ma, Baiping (Frontiers in Chemistry, 2023)
The rhizoma of Polygonatum odoratum (PO) is used to treat yin injuries of the lung and stomach in traditional Chinese medicine. The chemical constituents of this herb are steroidal saponins, homoisoflavanones, and alkaloids. Xiangyuzhu (XPO) and Guanyuzhu (GPO) are available in the market as two specifications of the commodity. Nonetheless, systematic research on the identification and comparison of chemical constituents of these two commercial specifications is yet lacking. Herein, an integrated method combing ultra-high-performance liquid chromatography-quadruple time-of-flight mass spectrometry (UHPLC-Q-TOF/MS) with ultra-high-performance liquid chromatography-charged aerosol detection (UHPLC-CAD) was employed for the comprehensively qualitative and quantitative analyses of PO. A total of 62 compounds were identified by UHPLC-Q-TOF/MS, among which 13 potential chemical markers were screened out to distinguish two commercial specifications. Subsequently, the absolute determination method for polygodoraside G, polygonatumoside F, and timosaponin H1 was established and validated by UHPLC-CAD. The contents of the three compounds were 13.33–236.24 μg/g, 50.55–545.04 μg/g, and 13.34–407.83 μg/g, respectively. Furthermore, the ratio of timosaponin H1/polygodoraside G could be applied to differentiate the two specifications. Samples with a ratio <2 are considered XPO and >5 are considered GPO. Therefore, the above results provide a valuable means for the quality control of PO.